(untitled) (INTERNATIONAL SEMINAR, 2025)
This study aims to conceptually analyze how PSAK 109 based zakat reporting accountability influences the level of trust that muzakki place in zakat institutions in Indonesia. The research is grounded in the persistent gap between the national potential and actual collection of zakat, which is largely attributed to limited transparency, weak governance, and varying levels of professionalism among zakat management organizations. Using a qualitative approach through an integrative literature review, this study synthesizes insights from academic publications, books, institutional reports, regulatory documents, and theoretical discussions related to Islamic accounting and zakat governance. The analysis employs thematic content analysis and theory driven synthesis to explore the role of PSAK 109 as a financial reporting standard that provides structured guidance on the recognition, measurement, presentation, and disclosure of zakat funds. The findings indicate that PSAK 109 enhances the clarity, consistency, and accountability of financial reporting in zakat institutions, although its implementation remains uneven, particularly among smaller institutions with limited technical capacity. The reviewed literature consistently highlights that muzakki perceptions of transparency, accountability, and professional management are fundamental determinants of trust in zakat institutions. Based on these insights, the study proposes that higher levels of PSAK 109 based reporting accountability, as perceived by muzakki, lead to greater trust in zakat institutions. These conceptual findings offer important implications for strengthening governance practices and provide directions for future empirical research aimed at validating this proposed relationship.